Mecanismos De Regeneração Natural Em Cronossequência De Áreas Pós-Cafeicultura Em Floresta Ombrófila Densa, ES - Sales, Denyse Cássia De Maria (2024)
Coffee cultivation is a prominent agricultural activity in Espírito Santo. Therefore, it is important to understand how the regeneration of abandoned environments occurs after land use for this cultivation. This study aimed to investigate changes in floristic composition and horizontal structure in the regenerative stratum and the soil seed bank (SSB), in a chronosequence of forests post-abandonment of Arabica coffee cultivation, located in Venda Nova do Imigrante, southern Espírito Santo. Four fragments with different ages since abandonment after coffee cultivation, 20 (F20), 35 (F35), 60 years (F60), and a reference area (REF), were selected. Ten plots of 25 m² each were installed in each of the areas. In regeneration, all shrub-tree individuals with a height ≥ 50 cm and up to 2.5 cm diameter at breast height (DBH) were measured, identified, and classified according to successional group, life form, and threat level. In the SSB, 40 composite samples, one per plot, were collected in two periods, using a template of 25 x 25 x 8 cm. In the nursery, under 50% shade, samples were placed in trays to assess germination over seven months. Phytosociological parameters, Shannon diversity (H'), Pielou evenness (J), Margalef richness (R), and floristic similarity were evaluated. To check the interaction between natural regeneration and environmental variables, canopy openness and physicochemical soil analysis were assessed. From this, a redundancy analysis was performed. In natural regeneration, between the F35 and REF fragments, H' varied from 2.1 to 3.8, J varied from 0.6 to 0.9, and R varied from 5.4 to 13.9, respectively. Rubiaceae was among the families with the most individuals in all areas. The species with the highest Importance Value varied between areas. Tree species (72.7%), late secondary (22.3%), and Least Concern at the threat level (37%) were predominant in all fragments. Only six species occurred in all fragments. For the seed bank, H' index varied from 3 to 3.4, J was 0.9, R varied from 5.4 to 7.3 across all areas. There was a difference in the density of germinated seeds between the rainy period (79.8 individuals.m-2) and the less rainy period (318.51 individuals.m-2). The family with the greatest richness was Asteraceae, the species with the highest VI in the less rainy period was Cecropia hololeuca, and in the rainy period was Emilia sonchifolia. There was sharing of nine species among all areas. The environmental variables that had the greatest influence on vegetation were soil moisture, canopy openness, soil density, calcium, magnesium, sodium, potential acidity, and aluminum. There is potential for areas abandoned after coffee cultivation to be regenerated, as demonstrated by the values of diversity, evenness, and dominance obtained. Additionally, the high number of late species demonstrates that abandonment time equal to or greater than 20 years is promising for the quality of regeneration of these environments. However, the difference in species composition confirms data obtained in other studies that it is one of the last elements to be recomposed, and the species that will form the secondary forest are unlikely to be the same as those of the primary vegetation.